Quasi-static modeling of spur gear time varying strength analysis - Lias, M.R. (Asian Research Publishing Network, 2017)
Measurement of gear tooth strength is important procedures in a preliminaries gear design. Two components of spur gear time-varying strength known as tooth surface contact stress (TSCS) and tooth root bending stress (TRBS) can be evaluated using an analytical or finite-element method (FEM). With the advent of computerization era; many researchers turned to finite-element modeling as the important tool in gearing studies. Two different modeling approach commonly used was based on static or dynamics application to the finite-element solution. Both solution are capable to offer several output results and interpretation. However, the complexities of the gear tooth may cause the modeling to imperfect zone of assumption. Therefore, the main aim of this study is to develop a new simple quasi-static modeling based on ANSYS Workbench. The objective was to conduct the analysis of time-varying strength of the spur gear system and compare to the analytical equations. The critical location (CL) for each strength property was also investigated. As the result, the proposed modeling was in a good agreement to the analytical model and reliable to conduct the spur gear time-varying strength analysis. © 2006-2017 Asian Research Publishing Network (ARPN). All rights reserved.